Implementation of the ATIK model in improving the mastery of new vocabulary in early childhood through flashcards - Lestari, Selvi; Qonita, Hanna Adha; Islamy, Yayang Chisva; Sa'adah, Khaila Nuriyatul; Watini, Sri (Jurnal Ilmiah Mandala Education (JIME), 2024)
Vocabulary is one of the important aspects of language development in children. Good vocabulary skills will support children's ability to communicate, think, and learn. This study aims to improve mastery of new vocabulary in early childhood using Flashcard media. The reason for this study is because of the low vocabulary in early childhood, which is caused by the lack of utilizing learning media that already exist today. In this study using "Model ATIK" stands for Observe, Imitate and Work (ATIK). This research method uses the PTK method (Research, Action and Class), while this method consists of 3 stages, namely 1). Listen stage, 2). Speech stage, 3). Speech and point stage. Implementation in this activity is carried out in 3 cycles. Cycle I children are able to listen, able to pronounce new vocabulary by looking at flashcards and able to pronounce when instructed by the teacher 58.1%. Cycle II children were able to pronounce new vocabulary by looking at flashcards without being instructed by the teacher 72.2%. Cycle III children are able to pronounce new vocabulary by looking at flashcards and are able to show flashcard pictures when the teacher utters new vocabulary 88.7%.